Beyond emotions in language psychological verbs at the interfaces - Rozwadowska, Bożena; Bondaruk, Anna (Linguistik aktuell ;, 2020)
"This book sheds new light on the puzzle of psychological predicates in a cross-linguistic perspective by looking at them from a variety of angles at the interfaces between event structure, lexical and viewpoint aspect, syntax and information structure. The individual chapters focus on Polish and Spanish psych verbs, which manifest new overt contrasts that often remain covert in languages such as English, e.g., aspectual distinctions, the peculiarities of dative constructions, or the role of information structure in determining the word order. One of the main contributions of the book lies in positing a new typology of basic event types enriched with the initial boundary events. Moreover, due attention is devoted to dative experiencers as compared to accusative experiencers. Although couched in the generative tradition, the main insights presented in this collection are theory neutral and may be of interest to linguists of all persuasions"--